2006
DOI: 10.1177/0886260505285724
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Use, Self-Reported Violent Crime, and Recidivism Among Offenders in California Who Abuse Substances

Abstract: This study uses data from 641 state prison parolees in California to examine the associations between methamphetamine use and three measures of criminal behavior: (a) self-reported violent criminal behavior, (b) return to prison for a violent offense, and (c) return to prison for any reason during the first 12 months of parole. Methamphetamine use was significantly predictive of self-reported violent criminal behavior and general recidivism (i.e., a return to custody for any reason). However, methamphetamine u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(78 citation statements)
references
References 22 publications
5
72
0
1
Order By: Relevance
“…One study examined 146 deaths in which MA was detected in the blood and found that 27% were homicides and 15% were suicides [26] . In a study of 404 parolees, after adjusting for involvement in the drug trade, MA use in the previous 30 days was predictive of self-reported violent crime and general recidivism but was not predictive of return to custody for violent crime [27] . In a Japanese study of 1,362 youth in a 'classification home' (a home for juvenile delinquents), those with a history of MA use were less likely to have experienced violence [28] .…”
Section: Discussionmentioning
confidence: 99%
“…One study examined 146 deaths in which MA was detected in the blood and found that 27% were homicides and 15% were suicides [26] . In a study of 404 parolees, after adjusting for involvement in the drug trade, MA use in the previous 30 days was predictive of self-reported violent crime and general recidivism but was not predictive of return to custody for violent crime [27] . In a Japanese study of 1,362 youth in a 'classification home' (a home for juvenile delinquents), those with a history of MA use were less likely to have experienced violence [28] .…”
Section: Discussionmentioning
confidence: 99%
“…15 A recent study estimated that nearly 25 million people worldwide have used amphetamines in the past 12 months, making it the most widely used illicit drug after cannabis. 18 In a study by Cartier et al, 19 use of the methamphetamine was significantly predictive of self-reported violent criminal behavior. Intoxication with methamphetamine is often accompanied by disinhibition, agitation, and paranoia and these effects may lead to violent behavior.…”
Section: Discussionmentioning
confidence: 96%
“…神兴奋剂,具有很强的精神毒性和神经破坏作用,对成瘾者的身体、行为和精神等方面都会产生一系列 的破坏性反应,包括心血管和呼吸问题、抽搐、牙齿和皮肤溃烂、攻击行为、冒险寻求、性冲动、各类 精神疾病以及记忆力下降等 (Winslow, Voorhees, & Pehl, 1988;Watt, Guidera, Hobkirk, Skinner, & Meade, 2016;Colfax & Shoptaw, 2005)。其中,攻击或暴力行为是冰毒成瘾者较为突出的行为表现,国内外众多 研究结果支持滥用冰毒会导致成瘾者产生高水平的暴力和攻击行为 (Boles, & Miotto, 2003;Cartier, Farabee, & Prendergast, 2006;王玮,肇恒伟,李晨,赵子阳,2017) …”
Section: 引言 冰毒(即甲基苯丙胺,又名脱氧黄麻碱,Methamphetamine)属于苯丙胺类的兴奋剂,是当前流行较为 广泛的一unclassified